A physical biomarker of the quality of cultured corneal endothelial cells and of the long-term prognosis of corneal restoration in patients - Yamamoto, Akihisa; Tanaka, Hiroshi; Toda, Munetoyo; Sotozono, Chie; Hamuro, Junji; Kinoshita, Shigeru; Ueno, Morio; Tanaka, Motomu (Nature biomedical engineering, 2019)
Dysfunction of the corneal endothelium reduces the transparency of the cornea and can cause blindness. Because corneal endothelial cells have an extremely limited proliferative ability in vivo, treatment for corneal endothelial dysfunction involves the transplantation of donor corneal tissue. Corneal endothelium can also be restored via intraocular injection of endothelial cells in suspension after their expansion in vitro. Yet, because quality assessment during the expansion of the cells is a destructive process, a substantial number of the cultured cells are lost. Here, we show that the ‘spring constant’ of the effective interaction potential between endothelial cells in a confluent monolayer serves as a biomarker of the quality of corneal endothelial cells in vitro and of the long-term prognosis of corneal restoration in patients treated with culture-expanded endothelial cells or with transplanted corneas. The biomarker can be measured from phase contrast imaging in vitro and from specular microscopy in vivo, and may enable a shift from passive monitoring to pre-emptive intervention in patients with severe corneal disorders.
Gesehen am 06.02.2020